Legal and Administrative Factors of the Transformation of the Content of Education under the Pressure of the COVID-19 Pandemic - Didiuk , Iryna; Bekh , Yuliya; Zhyzhko , Tetiana; Kravchenko, Alla; Kurhan-Bakoveieva , Yana; Kyzymenko, Iryna (Journal of Ecohumanism, 2024)
The objective of this study is to examine the administrative and legal aspects impacting the transformation of educational content and form during the COVID-19 pandemic, with the aim of understanding their role in adapting educational systems to crisis conditions. This research is grounded in administrative law and educational theory, exploring how legal frameworks and administrative policies have shaped educational transformations during the pandemic. The IDEF0 method, a functional modeling methodology, provides a structured approach to analyzing these transformations. The methodology adopted for this research utilizes the IDEF0 method to model the administrative and legal influences on education during the pandemic. This approach involves a detailed analysis of existing legal documents, administrative guidelines, and educational policies that have been implemented in response to COVID-19. The analysis resulted in the development of an IDEF0 model that maps the key administrative and legal factors influencing educational transformation. The discussion contextualizes these findings within the broader framework of emergency education response and administrative law, highlighting the dynamic interplay between legal mandates and educational practices. The implications of this research are significant for policymakers and educational administrators as they provide insights into the effective legal and administrative strategies that can support educational continuity in crisis situations. These findings can inform future legislative and policy-making processes to enhance the resilience of educational systems. This study contributes to the literature by employing the IDEF0 method to model the influence of administrative and legal frameworks on education during a global health crisis.